2005
DOI: 10.1145/1101779.1101783
|View full text |Cite
|
Sign up to set email alerts
|

Practical knowledge management tool use in a software consulting company

Abstract: is a research scientist with SINTEF Technology and Society in Trondheim, Norway.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Software development processes have always been knowledge-intensive [6,19,42]. For one thing, the increased complexity of SE project work has led to a greater reliance upon knowledge processes to solve problems [15,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Software development processes have always been knowledge-intensive [6,19,42]. For one thing, the increased complexity of SE project work has led to a greater reliance upon knowledge processes to solve problems [15,20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the participants were also asked to complete a detailed questionnaire in order to gain an understanding of the current KM practices within their company. During the data collection we also focused on both codifying and personalising knowledge strategies [19,22]. Specific objectives of this study are: (a) to determine current practices for KM in SE in Australian companies, (b) to describe activities that comprise the KM process for SE in these companies, (c) to identify high-level models of the KM process for SE and (d) to establish the impact of leadership, technology, culture and measurement as enablers of the KM process for SE in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…A study of a skills management system found that this tool was in use for a variety of purposes, from allocating resources, searching for competence, identifying project opportunities, to upgrading skills [14]. The tool was found to enable learning both at individual and company level.…”
Section: Knowledge Management In Global Software Developmentmentioning
confidence: 99%
“…In the scientific literature, a number of initiatives have been for implementation have been considered in Knowledge Management systems and, particularly, for Competency Management in Software Engineering (Rus & Lindvall, 2002), (Lindgren, Stenmark, & Ljungberg, 2003), (Aurum, Parkin, & Cox, 2004) & (Dingsøyr, Djarraya & Røyrvik, 2005).…”
Section: Assessmentmentioning
confidence: 99%